PROPHETIC LEADERSHIP: A REVIEW OF ITS ROLE IN IMPROVING ISLAMIC EDUCATION INSTITUTIONS IN INDONESIA - Murni Murni; Adiyono Adiyono (Adisam Publisher, 2023)
This literature review aims to examine the concept of prophetic leadership and its role in improving Islamic education institutions in Indonesia. The review is based on a comprehensive analysis of existing literature from various sources, including academic journals, books, and government reports. The study identifies key themes and trends related to prophetic leadership and its impact on Islamic education institutions in Indonesia. The review also discusses the challenges and limitations of implementing prophetic leadership principles in these institutions and proposes recommendations for future research and practice. future research should focus on developing practical guidelines for implementing prophetic leadership principles in Islamic education institutions in Indonesia while addressing any potential challenges or limitations that may arise during implementation efforts. These guidelines should be based on a comprehensive analysis of existing literature from various sources, including academic journals, books, and government reports, and should be designed to meet the specific needs of Islamic education institution leaders in Indonesia. The guidelines should also be accessible and affordable for all stakeholders, including those from low-income backgrounds or rural areas, and should promote accountability, transparency, financial sustainability, community engagement, leadership skills development, and innovation in Islamic education institutions in Indonesia.